2005
DOI: 10.1203/01.pdr.0000180554.16652.4e
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Changes after Pediatric Cardiac Surgery with Cardiopulmonary Bypass: Is Slow Wave Activity Unfavorable?

Abstract: Pediatric cardiac surgery with cardiopulmonary bypass (CPB) is frequently associated with neurologic deficits. We describe the postoperative EEG changes, assess their possible causes, and evaluate their relevance to neurologic outcome. Thirty-one children and five neonates with congenital heart disease were included. EEG recording started after intubation and continued until 22-96 h after CPB. In addition to conventional analysis, spectral analysis was performed for occipital and frontal electrodes, and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…NCS may be even more common than convulsions in patients with congenital heart disease (Helmers, Wypij, Constantinou, et al 1997, Gaynor, et al 2005, Clancy, et al 2005, Chock, et al 2006, Schmitt, et al 2005, Gunn, et al 2012). In the D-transposition of the great arteries study mentioned above, 136 of 171 infants underwent cEEG for 48 hours, and electrographic seizures occurred in 20%.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…NCS may be even more common than convulsions in patients with congenital heart disease (Helmers, Wypij, Constantinou, et al 1997, Gaynor, et al 2005, Clancy, et al 2005, Chock, et al 2006, Schmitt, et al 2005, Gunn, et al 2012). In the D-transposition of the great arteries study mentioned above, 136 of 171 infants underwent cEEG for 48 hours, and electrographic seizures occurred in 20%.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…[53] A study of children who underwent cardiac surgery with cardiopulmonary bypass and underwent EEG from intubation until 22–96 hours after bypass reported ES in 8% of 36. [54] Finally, a study of 39 infants undergoing Norwood-type operations and continuous amplitude-integrated EEG identified intraoperative seizures in 23% and postoperative seizures in 18%. [55] Risk factors for seizures in children with congenital heart disease include co-existing genetic defects, aortic arch obstruction, the presence of a ventricular septal defect, treatment with deep hypothermic circulatory arrest rather than continuous cardiopulmonary bypass and prolonged deep hypothermic circulatory arrest.…”
Section: Epidemiology Of Electrographic Seizures and Status Epilepticusmentioning
confidence: 99%
“…Schmitt et al reported alarmingly high rates of postoperative acute and permanent neurologic complications in children with CHD, including tetralogy of Fallot, ventricular septal defect, tricuspid atresia, anomalous pulmonary veins, and atrial septal defect [28]. None of these children had any known neurologic abnormalities preoperatively.…”
Section: Neurologic and Neurodevelopmental Outcomes After Cardiac Surmentioning
confidence: 99%
“…Postoperative EEG monitoring detects seizures that clinically would be missed due to pharmacologic neuromuscular blockade and sedation, including subclinical seizure activity [28]. Seizures may occur secondary to cerebral injury and worsen pre-existing or ongoing neuronal damage.…”
Section: Electroencephalogrammentioning
confidence: 99%
See 1 more Smart Citation